NAFKAH ANAK BAGI PASANGAN KAWIN SIRI MENURUT MAZHAB SYAFI’I (STUDI PUTUSAN PENGADILAN AGAMA NO. 0882/PDT.G/2020/PA.MLG DAN NO. 289/PDT.G/2019/PA.PBM) - Annaufal, Muhammad; Husaini, Akhmad (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study analyzes the differences between the rulings of the Religious Court of Malang (No. 0882/Pdt.G/2020/PA.Mlg) and the Religious Court of Prabumulih (No. 289/Pdt.G/2019/PA.Pbm) concerning the obligation of child support from unregistered marriages (siri), which reveal a tension between formal-legal and substantial-normative judicial approaches. The research focuses on examining the judges' legal considerations in both rulings and linking them to the principles of the Shafi'i school of jurisprudence (fiqh) and positive law in Indonesia. Using a normative legal approach and descriptive qualitative methods, secondary data was collected from copies of the court rulings cited in a thesis, as well as from fiqh literature, journals, and legislation. The results indicate that the Malang Religious Court granted the claim for child support based on the establishment of lineage through paternal acknowledgment, aligning with the Shafi'i school's view that considers the obligation of support as the child's luzum (inherent and permanent) right. Conversely, the Prabumulih Religious Court rejected the claim due to the absence of official marriage registration, reflecting a formalistic approach that overlooks substantive aspects. Therefore, this study concludes that courts which prioritize the establishment of lineage, including through scientific evidence, are more aligned with the objective of Islamic law (maqasid al-shari'ah) to protect the rights of the child. ABSTRAKPenelitian ini menganalisis perbedaan putusan Pengadilan Agama Malang (No. 0882/Pdt.G/2020/PA.Mlg) dan Pengadilan Agama Prabumulih (No. 289/Pdt.G/2019/PA.Pbm) terkait kewajiban nafkah anak dari pernikahan siri, yang menunjukkan adanya ketegangan antara pendekatan hukum formal-legal dan substansial-normatif. Fokus penelitian ini adalah mengkaji pertimbangan hukum hakim dalam kedua putusan tersebut dan mengaitkannya dengan prinsip-prinsip fikih mazhab Syafi’i dan hukum positif di Indonesia. Dengan menggunakan pendekatan hukum normatif dan metode kualitatif deskriptif, data sekunder dikumpulkan dari salinan putusan yang dikutip dalam tesis serta literatur fikih, jurnal, dan perundang-undangan. Hasilnya menunjukkan bahwa Putusan PA Malang mengabulkan gugatan nafkah dengan dasar pembuktian nasab melalui pengakuan ayah, sejalan dengan pandangan mazhab Syafi’i yang menganggap kewajiban nafkah sebagai hak anak yang bersifat luzum (tetap). Sebaliknya, Putusan PA Prabumulih menolak gugatan karena ketiadaan pencatatan resmi, mencerminkan pendekatan formal yang mengabaikan aspek substansial. Dengan demikian, penelitian ini menyimpulkan bahwa pengadilan yang mengedepankan pembuktian nasab, termasuk melalui bukti ilmiah, lebih sesuai dengan tujuan syariat (maqasid syari’ah) untuk melindungi anak.